Complications in Bariatric Surgery (Springer International Publishing, 2018)
This text focuses on the complications following bariatric surgery. The focus is on the immediate and long term complications that would be important to both the general surgeon and those surgeons with specialty experience in bariatric surgery. Sections address the nutritional deficiencies following bariatric surgery with specific attention to Roux en Y gastric bypass and pancreatico-biliary diversion as well as the correction of these deficiencies with medical intervention as well as the indications for surgical revision or reversal. The text reviews the work-up of a bariatric patient with abdominal pain including the appropriate imaging and threshold for operative intervention and the techniques to achieve optimal visualization during this difficult situation. This section focuses on the operative management of anastomotic and staple line leaks and how to definitively manage these surgical emergencies as well as achieve source control and stabilization. Later chapters focus on specific complications following bariatric surgery with specific focus on RYGB, vertical sleeve gastrectomy (VSG), biliary pancreatic diversion, and gastric band. Complications include gastric fistula, gastric staple line disruption following VSG, gastro-jejunal leak following RYGB, relux following bariatric surgery, and failure of weight loss following bariatric surgery. These sections are written by experts in the field of bariatrics and include evidence based medicine as well as expert opinion on the management of bariatric complications. The sections provide a review of the literature and references at the close of each section. Complications in Bariatric Surgery will serve as a resource for both the general surgeon who handles bariatric emergencies as well as the bariatric specialist.